Dietary Substitutions for Refined Carbohydrate That Show Promise for Reducing Risk of Type 2 Diabetes in Men and Women, , - Maki, Kevin C; Phillips, Alyssa K (The Journal of Nutrition, 2015)
Both genetics and lifestyle contribute to type 2 diabetes (T2D), a condition of elevated circulating glucose induced by a collection of metabolic defe…